Apis mellifera discrimination between flowers of commercial types of melon and implications to crop pollination - Fernandes, Nayanny; Pinto, Gercy; Zocolo, Guilherme; Aragão, Fernando Antonio; Freitas, Breno (Revista Ciência Agronômica, 2020)
We investigated the foraging pattern of A. mellifera in five commercial types of melon (Yellow, Cantaloupe, Charentais, Galia and Piel de Sapo) grown side by side. We also observed if this bee species can discriminate between flowers of the five melon types and if it shows preference for flowers of any of them. Results showed that the bees visit flowers of all types of melon throughout the day collecting pollen and nectar in similar foraging patterns. However, they visited significantly more flowers of the Cantaloupe type followed by the types Piel de Sapo and Yellow, while the melons type Galia and Charentais were the least visited by the bees. This behavior has implications for the use of A. mellifera for melon pollination, requiring that the bees be managed according to the type of melon cultivated. It also highlights the need to find out what makes flowers of some melon types to be more visited than others in order to select within the less visited types of melon for cultivars more attractive to the bees.